Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1200/jco.2016.68.5081
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Therapy Followed by Resection Versus Upfront Resection for Resectable Pancreatic Cancer: A Propensity Score Matched Analysis

Abstract: Background and aim: To compare cancer-specific survival (CSS) between patients who received neoadjuvant radiation followed by resection (NRR) and those who received upfront resection (UR) for locally advanced pancreatic cancer (LAPC). Methods: A total of 772 LAPC patients who underwent curative-intent surgical resection with or without neoadjuvant radiation from 2004 to 2013 were identified from the Surveillance, Epidemiology, and End Result (SEER) database. Propensity score matching (PSM) was conducted to eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
286
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(302 citation statements)
references
References 24 publications
11
286
2
3
Order By: Relevance
“…NAC prior to resection is associated with a significant survival benefit compared with upfront resection in patients with early-stage, resected PDAC (29). Several randomized studies comparing various NAC regimens with upfront surgery are in progress around the world.…”
Section: α-Smooth Muscle Actin (αSma) Expression According To Treatmementioning
confidence: 99%
“…NAC prior to resection is associated with a significant survival benefit compared with upfront resection in patients with early-stage, resected PDAC (29). Several randomized studies comparing various NAC regimens with upfront surgery are in progress around the world.…”
Section: α-Smooth Muscle Actin (αSma) Expression According To Treatmementioning
confidence: 99%
“…Furthermore, the proportion of patients with neadjuvant chemotherapy who were deemed resectable at laparotomy varies between 38% and 89% (32). Nevertheless, recently Mokdad and co-workers have shown that the use of neoadjuvant chemotherapy for localized, resectable PDAC has been associated with improved survivals (62). Conversely, a recent systematic review and meta-analysis has shown no potential benefit of neoadjuvant therapy for resectable PDAC (63).…”
Section: Neoadjuvant Therapies In Pdacmentioning
confidence: 97%
“…Use of neoadjuvant chemotherapy before surgical resection-an approach with growing utilization-is highlighted in the article by Mokdad and colleagues. 6,7 Postoperative chemotherapy improves survival in patients with resected pancreatic cancer, but adjuvant treatment can be limited by postoperative complications, poor tolerance, and early disease recurrence. To improve compliance with systemic therapy, address occult micrometastatic disease earlier in the treatment course, and better select patients for surgical resection, an alternative approach of delivering therapy before resection has been advocated.…”
Section: Challenges In Diagnosis and Managementmentioning
confidence: 99%
“…The authors used propensity score matching to control for baseline differences in the two groups and demonstrated a modestly increased survival among patients who received neoadjuvant therapy. 6 Although these findings are a valuable addition to the literature, inherent limitations of the nonrandomized retrospective design temper their immediate applicability to practice and, at the same time, further support the need for well-designed randomized studies that evaluate the neoadjuvant treatment approach.…”
mentioning
confidence: 99%